PERAN KREATIVITAS DAN INOVASI PELAKU USAHA DALAM DIVERSIFIKASI PRODUK PADA KEDAI STEAK & CHICKEN DI KAB. MAGETAN TAHUN 2014 (IMPLEMENTASI PENDIDIKAN KEWIRAUSAHAAN) - Sarijani, Endang; M.Si, Baedhowi; Sawiji, Hery (Jurnal Pendidikan Insan Mandiri, 2015)
Culinary business is the most desirable business by people today as it does not recognize any season and trend. Food currently is not merely a consumption product to fulfill the biological need of human beings, but has to do with a new life style, that is, becoming a culinary industry which not only gives a taste but also becomes a self-actualization need. Therefore, entrepreneurial spirits, creativity touches, and innovations are required in its process so that the business can sustainably be retained. The objective of this research is to investigate the role of creativity and innovation for product diversification at Steak & Chicken Stall by its owner.             This research used the descriptive research method. The samples of research were taken by using the non-probability sampling techniques consisting of accidental sampling for customers and purposive sampling for the owner and employees of the stall, Head of the Office of Industry and Trade of Magetan Regency. The data of research were gathered through in-depth interview, observation, and documentation. They were analyzed by using the interactive model of analysis.            The result of research shows that creativity and innovation are very much required for product diversification, as they can create new ideas for culinary products.  This in turn will increase the sale turnover and income. Product diversification is truly needed if the business condition begins to be threatened by new competitors or to be left by customers. To fix it, a self-exploration attitude is required, that is, the ability to sharpen creativities and implement them in real actions as an embodiment of innovations, so as to have special contributions to the increase of sale turnovers, customers, and profits.Keywords: Creativity, innovation, entrepreneurship, and product diversification